Biocompatible Materials: Microchannel and Nanofiber Array Morphology Enhanced Rapid Superspreading on Animals' Corneas (Adv. Mater. 23/2021). Issue 23 (8th June 2021) - Miao, Weining; Zheng, Shuang; Zhou, Jiajia; Zhang, Bo; Fang, Ruochen; Hao, Dezhao; Sun, Li; Wang, Dianyu; Zhu, Zhongpeng; Jin, Xu; Tian, Ye; Jiang, Lei
Abstract : In article number 2007152, Ye Tian and co‐workers report a rapid superspreading effect on animals' corneas that is endowed with a microchannel and nanofiber array morphology; superspreading is facilitated by the nanofiber array and the spreading speed is determined by the microchannel. The photo and scanning electron microscopy images of the cornea demonstrate the nanofiber array surrounded by hexagonal microchannels.